In Vitro Anti-Bacterial Activity of Root And Aerial Parts of Scrophularia Striata Bioss on Escherichia Coli, Staphylococcus Aureus and Bacillus Cereus - F Safavi; P Ebrahimi; H Mighani (Armaghane Danesh Bimonthly Journal, 2013)
Abstract